Effectiveness of Productive Zakat in Increasing the Economic Independence of Mustahik at Baznas Mataram City - Mukhlishin, Mukhlishin (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2024)
This study aims to describe how effective the productive zakat management program implemented by the National Zakat Agency (BAZNAS) of Mataram City is in strengthening the economic independence of mustahik. The main focus of this study is to explore the impact of the program on increasing the income and economic independence of mustahik in Mataram City. The main question to be answered in this study is how effective the productive zakat program is in encouraging the economic independence of mustahik and its influence on increasing the income of mustahik. Using a descriptive qualitative approach, this study collected data through interviews, observations, and documentation. The results of the study revealed that the productive zakat management program managed by BAZNAS Mataram City has proven to be effective in increasing the income and economic independence of mustahik, as seen from the increase in mustahik's income after receiving productive zakat assistance,which also contributes to empowering the local economy and reducing poverty in Mataram City. This program has proven to have a positive impact on mustahik, helping mustahik towards a more prosperous and independent life.